Analysis of Tourist Satisfaction as a Basis for Tourist Destination Development at the Sekumpul Waterfall Tourist Object, Buleleng, Bali - Komang Yuda Widiarta; I Wayan Ruspendi Junaedi; Christimulia Purnama Trimurti; Gusti Ngurah Joko Adinegara (The Eastasouth Management and Business, 2026)
Managing natural tourism destinations requires a balance between tourist expectations and management performance. Tourist satisfaction is a crucial indicator of management success, particularly for destinations that rely on natural beauty and firsthand experiences as their primary attractions. Sekumpul Waterfall, as a leading natural tourism destination in Bali, faces challenges in maintaining the quality of services and tourism experiences to meet diverse tourist expectations. This study aims to analyze the level of tourist satisfaction and compliance with the management of Sekumpul Waterfall. A quantitative approach was used, collecting data through tourist questionnaires. Data analysis was conducted using Importance Performance Analysis (IPA) to measure the alignment between importance and performance of satisfaction attributes, and the Customer Satisfaction Index (CSI) to measure overall tourist satisfaction. The results showed that the level of compliance with tourist satisfaction attributes reached 85.2%, falling into the “very appropriate” category, indicating that the destination management's performance has generally met tourist expectations. The tourist experience and attractions are key strengths, while responsiveness of service, cleanliness of facilities, and infrastructure maintenance still require attention. A CSI score of 67.4% indicates that tourists are satisfied, although improvements are still needed in several attributes. These findings support Expectancy Disconfirmation Theory (EDT), which states that satisfaction is formed through a comparison between expectations and actual performance. Practically, this research provides implications for destination managers to prioritize improvements to attributes with performance gaps, while maintaining the excellence of the natural tourism experience to achieve sustainable tourist satisfaction.